2020
DOI: 10.3389/fneur.2020.569432
|View full text |Cite
|
Sign up to set email alerts
|

Familial Idiopathic Intracranial Hypertension in Two Non-obese Chinese Sisters

Abstract: Background: Familial idiopathic intracranial hypertension (FIIH) is a rare condition, the etiology of which is unclear.Aims: To describe two non-obese Chinese sisters who met the criteria of FIIH and to analyze the clinical features and prognosis of FIIH.Methods: The clinical course, treatment, and prognosis of these two patients were analyzed retrospectively. Meanwhile, all the literature of familial IIH (FIIH) was reviewed.Results: These two sisters presented with headaches and visual impairment in their mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Only a small number of literature reports about IIH in non-obese young women. Other instances of rare cases of IIH are familial or genetic predisposition, including atypical demographics such as men and older people [7,8]. One study reported that IIH may be diagnosed in older patients with normal Body Mass Index (BMI) because there is a lower suspicion index in the normal BMI population [8].…”
Section: Discussionmentioning
confidence: 99%
“…Only a small number of literature reports about IIH in non-obese young women. Other instances of rare cases of IIH are familial or genetic predisposition, including atypical demographics such as men and older people [7,8]. One study reported that IIH may be diagnosed in older patients with normal Body Mass Index (BMI) because there is a lower suspicion index in the normal BMI population [8].…”
Section: Discussionmentioning
confidence: 99%
“…erefore, as long as the syndrome type diagnosis of the disease was accurate, it was quite beneficial in the treatment effect of the disease. e results of many studies using TCM therapy show that the therapeutic effect of TCM therapy was better than that of simple western medicine therapy and had the characteristics of safety, effectiveness, and small side effects [25][26][27]. It also indicates that the incidence of adverse reactions in the acupoint application group (12%) had no significant statistical significance compared with the control group (10%) (P > 0.05), suggesting that there was no significant difference in the safety between acupoint application therapy and conventional western medicine.…”
Section: Discussionmentioning
confidence: 99%
“…This is also supported by previous reports of non-obese familial IIH. 4 , 5 , 6 , 12 Karaman et al have reported six nonobese family members with IIH based on papilledema, however, three of them were diagnosed “presumptively” as they declined lumbar puncture. 5 Beri et al have reported a mother and two daughters with IIH with no obesity; the first daughter with typical IIH presentation with papilledema and high CSF opening pressure while the second daughter had documented high CSF opening pressure but no papilledema.…”
Section: Discussionmentioning
confidence: 99%